PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL DAN KEBIJAKAN DIVIDEN TERHADAP KEBIJAKAN HUTANG PERUSAHAAN (Studi Pada Perusahaan Sektor Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Periode 2010-2013) - B11111085, RIA SEPTIANARIA SEPTIANA B11111085 (Jurnal Manajemen Update, 2015)
Factors of Ownership and Dividen Policy could have an impact on Debt Policy, depending on the severity of agency conflict. The purpose of this research was to find out the effect of managerial ownership, institutional ownership, and dividend policy on debt policy. Sample of 15 companies belongs to the consumption goods industry listed on Indonesia Stock Exchange is selected using the purposive sampling tehnique. Data analysis uses multiple reggresion model. The result shows that (1) manageÂrial ownership has a negative effect and significant on debt policy (2) institusional ownership has a positive effect but not significant on debt policy (3) dividend policy has a negative effect toward debt policy. Keywords : Manajerial Ownership, Institutional Ownership, Dividend Policy, and Debt Policy Â